Cytokine profile, ferritin and multi-visceral involvement characterize macrophage activation syndrome during adult-onset Still's disease. (19th April 2022) - Ruscitti, Piero; Ursini, Francesco; Berardicurti, Onorina; Masedu, Francesco; Bozzalla Cassione, Emanuele; Naldi, Susanna; Di Cola, Ilenia; Di Muzio, Claudia; De Stefano, Ludovico; Di Nino, Elena; Navarini, Luca; Vomero, Marta; et al.
Abstract: Objectives: To multidimensionally characterize macrophage activation syndrome (MAS) complicating adult-onset Still's disease (AOSD) considering cytokine profile, inflammatory markers and multi-visceral involvement of the disease. To perform a high-dimensional phenotypic analysis of circulating immune cells in AOSD patients with and without MAS. To assess interferon (IFN)-related pathways in AOSD synovial tissues by a bulky RNA sequencing. Methods: Clinical and biologic data were collected and compared in AOSD patients with and without MAS. Sera biomolecules were analysed by Luminex multiplexing technology. Mass cytometry (CyTOF) was used to characterize circulating immune cells. A bulky RNA sequencing was performed in AOSD synovial tissues. Results: Forty consecutive AOSD patients were assessed, 14 complicated with MAS. Paralleling with increases of systemic score and ferritin, MAS patients showed higher levels of IL-1α, IL-1β, IL-1Ra, IL-2Ra, IL-6, IL-10, IL-17A, IFN-γ, G-CSF, MCP-1, MIP-1α and SCF. Combining the discriminatory ability of these data in identifying MAS, the best model was composed by systemic score, ferritin, IFN-γ and IL-10. By CyTOF analysis, MAS patients showed an increase of circulating 'classical monocytes' and a reduction of total NK cells. Our assessment showed 3477 IFN-related genes (IRGs) were differently expressed in AOSD synovial tissues. Conclusions: A multidimensional characterization of AOSD patients suggested that IFN-γ, IL-10, ferritin and systemic score discriminated the occurrence of cytokine storm syndrome associated with MAS. The inflammatory milieu of AOSD and MAS may be related to a signature of circulating immune cells. Finally, our results about IRGs reinforced the role of IFN-γ in these patients.